Cyclopoid copepods (Nanaspididae and Sabelliphilidae) associated with holothurians in New Caledonia - Humes, Arthur G. (Washington Smithsonian Institution Press, 1975)
Smithsonian contributions to zoology; no. 202
Keywords: Crustacea; Nanaspididae; Sabelliphilidae